Characteristic component profiling and identification of different Uncaria species based on high‐performance liquid chromatography–photodiode array detection tandem ion trap and time of flight mass spectrometry coupled with rDNA ITS sequence. (15th November 2017) - Zhao, Bingqiang; Huang, Yanjun; Chen, Qiulan; Chen, Qizhao; Miao, Hui; Zhu, Shuang; Zeng, Changqing
Abstract: Uncaria is a multi‐source herb and its species identification has become a bottleneck in quality control. To study the identification method of different Uncaria species herbs through HPLC–MS coupled with rDNA Internal Transcribed Spacer (rDNA ITS) sequence, both plant morphological traits and molecular identification were used to determine the species of every collected Uncaria herb. The genetic analysis of different Uncaria species was performed using their rDNA ITS sequence as a molecular marker. Meanwhile, the phylogenetic relationships of 22 samples from six Uncaria species were divided and classified clearly. By optimizing the chromatographic conditions, a practical HPLC method to differentiate various varieties of Uncaria herbs was set up based on a set of characteristic components across each species. A high‐performance liquid chromatography–photodiode array detector tandem ion trap and time of flight mass spectrometry technique combined with reference substances was utilized to derive 21 characteristic compounds containing six groups of six Uncaria species in China. Thus, this study provides a feasible method to solve the current problem of confusion in Uncaria species, and makes a significant step forward in the appropriate clinical use, in‐depth research and further utilization of different Uncaria species.